Efficacy and safety of neoadjuvant immunotherapy combined with chemotherapy in locally advanced esophageal cancer: A meta-analysis - Wang, Jincheng; Zhang, Kun; Liu, Tianzhou; Song, Ying; Hua, Peiyan; Chen, Shu; Li, Jindong; Liu, Yang; Zhao, Yinghao (Frontiers in Oncology, 2022)
Objective: The progress of neoadjuvant therapy for resectable locally advanced esophageal cancer has been stagnant. There has been much progress in immunotherapy for advanced esophageal cancer, but the efficacy and safety of neoadjuvant immunotherapy for resectable locally advanced esophageal cancer have not yet been definitively demonstrated. Methods: Original articles describing the safety and efficacy of neoadjuvant immunotherapy in resectable locally advanced esophagus published until July 2022 were retrieved from PubMed, Embase, and the Cochrane Library. The ratio (OR) and 95% confidence interval (CI) were calculated to conduct heterogeneity and subgroup analysis. Results: In total, 759 patients from 21 studies were enrolled. The effectiveness of neoadjuvant immunotherapy in combination with chemotherapy was evaluated using the major pathologic response (MPR) and pathologic complete response (PCR). In the enrolled patients, 677 were treated surgically and 664 achieved R0 resection. Major pathological remission was achieved in 52.0% (95% CI: 0.44–0.57) of patients on neoadjuvant immunotherapy combined with chemotherapy and complete pathological remission in 29.5% (95% CI: 0.25–0.32) of patients. The safety was primarily assessed by the incidence of treatment-related adverse events (TRAEs) and surgical resection rates. The incidence of TRAEs and the surgical resection rate combined ORs were 0.15 (95% CI: 0.09–0.22) and 0.86 (95% CI: 0.83–0.89), respectively. Conclusion: Neoadjuvant immunotherapy combined with chemotherapy in locally advanced resectable esophageal cancer is effective and safe.